Penguatan Etika Berkomunikasi Dalam Pendidikan Tinggi Berbasis Karakter - Assa, Inriyanti; Tuturop, Katarina L; Kawulur, Hanna; Ayomi, Mina; Mamoribo, Sherly (UNIVERSITAS CENDERAWASIH, 2025)
This program aimed to strengthen the understanding and practical application of ethics and health communication among interdisciplinary students. Within the academic environment, effective communication and ethical behavior are fundamental in shaping students’ character as future leaders. The activity emphasized the importance of ethical communication, appropriate behavior, and dress code in campus interactions, particularly in relationships among students, faculty members, and administrative staff. Using a participatory approach, the program involved 57 students who engaged in lectures, discussions, and hands-on practice in composing academic messages. The material was delivered by three expert speakers in communication and health ethics. The results indicated an increased awareness among students regarding the significance of ethics and communication in building healthy, productive, and professional relationships within the campus environment. This article comprehensively discusses the background, implementation methods, and outcomes of the activity, which are relevant to strengthening students' interpersonal and ethical capacity. This approach is expected to serve as a cross-sectoral learning model for developing a socially, professionally, and ethically resilient young generation. Keywords: Ethics, Communication, Interdisciplinary